Experimental study on effect of pavement background on obstacle visibility in LED lighting environment of road tunnel - Shouzhong Feng; Deyuan Kan; Long Zhou; Xianling Liu; Cunyu Du; Weixing Mao (Underground Space)
The tunnel pavement is generally made of asphalt or concrete. Due to the relatively fixed material of pavement, the effect of tunnel pavement setting on the lighting environment and visual performance of drivers has not received sufficient attention, especially the impact on the visual performance of drivers during driving has not been revealed. Therefore, experimental research on the visual recognition performance of an obstacle on asphalt and concrete pavements inside tunnels during dynamic driving was conducted in this study. The results indicate that under the same pavement illumination, the luminance on concrete pavement is higher than that on asphalt pavement due to the higher reflectance of concrete. The visible distance of the human eyes for a gray obstacle with a reflectance of 0.2 on the concrete pavement is greater than that on the asphalt pavement, and the visible distance of the obstacle on the concrete pavement increases by more than 28%. When the color of the obstacle and the pavement are close, it can be challenging for observers to recognize the obstacle, and the pavement and obstacle need to have a higher level of luminance for the recognition. During dynamic driving, the visible distance at a speed of 60 km/h is 1.2 to 1.4 times that at a speed of 80 km/h, which means the influence of vehicle speed on the human eye’s recognition of obstacles on asphalt and concrete pavements should be taken into consideration in the design of road tunnel lighting. The correlated color temperature and S/P value of LED light have little impact on the visible distance of human eyes to the obstacle on the asphalt and concrete pavements, but it does create different visual perceptions. As the correlated color temperature and S/P value increase, the lighting environment of the tunnel gradually gives a brighter feeling to drivers.